Moral Dilemmas as a Didactic Strategy in the Process of Critical Reading and Inference - Sandoval-Fagua, Andrea-Isabel (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This article reveals the results obtained in the application of strategies for textual interpretation, comprehension and critical reading and inference in fourth grade elementary school students of the Sora Educational Institution in the municipality of Sora (Boyacá, Colombia). The application of the proposal allowed activating in them, the levels of comprehension and argumentation, through the revision and interpretation of written texts, in this case the moral dilemmas, used as a didactic strategy. Within the methodological process, two tests were applied: a diagnostic test and another one at the end of the development of the proposal; likewise, a didactic unit was developed, integrated by four reading workshops, which proposed various activities aimed at encouraging the critical and inferential process under the qualitative research methodology (action-research). Thus, with the final analysis of the results, some deficiencies were evidenced in the students of the base group, who after the didactic intervention, were able to establish comparisons, give reasons that could explain the dilemmas presented, identifying causes and consequences, favoring in them the ability to create and argue so that they could formulate reasoning and develop coherent. In conclusion, after the work developed, students improved their ability to read critically, taking different positions on each text, which is valid to apply in different areas of knowledge alternating in a synchronous way didactic and technological tools that can contribute to activate competent reading and writing. In the same way, critical and inferential reading allows them to reinforce the work by competences, that is to say, to know how to do in context.